Synthesis, Crystal Structure and DFT Studies of 8-chloro-3-((3-chlorobenzyl)thio)-[1,2,4]triazolo[4,3-a]pyridine - Jin-Xia Mu; Ming-Yan Yang; Zhao-Hui Sun; Cheng-Xia Tan; Jian-Quan Weng; Hong-Ke Wu; Xing-Hai Liu (Crystals, 2015)
8-chloro-3-((3-chlorobenzyl)thio)-[1,2,4]triazolo[4,3-a]pyridine was synthesized and recrystallized from EtOH. The compound was characterized by 1H NMR, 13C NMR, FTIR, MS, elemental analysis and X-ray diffraction. The compound was crystallized in the monoclinic space group P2(1)/c with a = 8.1992(5), b = 21.7731(12), c = 7.8454(6) Å, α = 90, β = 108.421(7), γ = 90°, V = 1328.81 (15)Å3, Z = 4 and R = 0.0351. Theoretical calculation of the title compound was carried out with B3LYP/6-31G. The full geometry optimization was carried out by using the 6-31G basis set. The frontier orbital energy and atomic net charges were discussed. The experimental results of the compound have been compared with theoretical results and it was found that the experimental data shows good agreement with the calculated values.